Nomenclature and Comparative Morphology of the Teneurin/TCAP/ADGRL Protein Families - Sita, Luciane V.; Diniz, Giovanne B.; Horta-Junior, José A. C.; Casatti, Claudio A.; Bittencourt, Jackson C. (Frontiers in Neuroscience, 2019)
The teneurins are a family of glycosylated type II transmembrane proteins synthesized in several tissue from both vertebrate and invertebrate species. These proteins interact with the latrophilins, a group of adhesion G protein-coupled receptors. Both teneurins and latrophilins may have been acquired by choanoflagellates through horizontal gene transfer from a toxin-target system present in prokaryotes. Teneurins are highly conserved in eukaryotes, with four paralogs (TEN1, TEN2, TEN3 and TEN4) in most vertebrates playing a role in the normal neural development, axonal guiding, synapse formation and synaptic maintenance. In this review, we summarize the main findings concerning the distribution and morphology of the teneurins and latrophilins, both during development and in adult animals. We also briefly discuss the current knowledge in the distribution of the teneurin C-terminal associated protein (TCAP), a peptidergic sequence at the terminal portion of teneurins that may be independently processed and secreted. Through the analysis of anatomical data, we drew parallels to the evolution of those proteins and the increasing complexity of this system, which mirrors the increase in sensory complexity. This review underscores the need for further studies investigating the distribution of teneurins and latrophilins and the use of different animal models.